On the asymptotic normality of the estimate of the spectral function - Bentkus, R. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Бенткус. Об асимптотической нормальности оценки спектральной функции R. Bentkus. Apie spektrinės funkcijos įvertinimo asimptotinį normalumą